RETRACTED: Understanding Barriers to PrEP Adherence: A Brief Report on the Combined Effects of Alcohol Misuse, PTSD, and Gut Microbiome Disruption in HIV Prevention - Hasan, Md Rakibul; Davidson, Richard (Queeva Publishing, 2025)
Background: Human Immunodeficiency Virus (HIV) remains a global health challenge. While Pre-exposure Prophylaxis (PrEP) offers high efficacy for prevention, its adherence is significantly impacted by gastrointestinal (GI) dysbiosis and hazardous alcohol use. Alcohol misuse exacerbates PTSD and behavioral health issues, and chronic alcohol use can escalate GI disturbances, potentially leading to severe conditions like alcoholic hepatitis. Methods: This brief report presents a conceptual analysis of existing literature and retrospective clinical data. Thematic coding was utilized to identify correlations between alcohol use, GI dysbiosis, PTSD, and PrEP adherence among HIV-negative individuals. Results: Hazardous alcohol use amplifies PTSD symptoms and disrupts gut microbiota, causing systemic inflammation and broader behavioral problems. These factors collectively compromise PrEP adherence, with affected individuals demonstrating rates as low as 45–60%, particularly in marginalized groups. Conclusion: Integrated behavioral interventions prioritizing alcohol reduction, microbiome support, and trauma-informed mental health care are crucial to optimize PrEP outcomes and advance HIV prevention efforts.